Effect of Spindle Speed, Feedrate, Tool Geometry, and Polyester & Vinylester Blends on Surface Roughness and Surface Hardness Alteration of the Hole - Adam Malik; Exel Athoriq; Muhammad Hafiz; Hairul Abral (METAL: Jurnal Sistem Mekanik dan Termal, 2023)
In this study, 2 types of polymers were mixed, namely polyester and vinylester called polyester-vinylester blend (PVB) as the test workpiece. The experiments carried out were testing the surface quality of the hole, namely surface roughness (Ra), and surface hardness alteration (SHA) after drilling. In this study, the effects of spindle speed (n) & feedrate (f), cutting-edge angle (Kr), and PVB composition (P%V%) were tested. The results showed that the factor that most influenced the surface roughness value was the feedrate with a contribution value of 39% and the PVB composition (32%) for PVB dominantly polyester. Whereas in vinylester dominant PVB, the most influential factor is the spindle speed (50%). For the measurement of surface hardness alteration that occurs, the factor that affects surface hardness alteration is the cutting-edge angle (44%) in PVB dominantly of polyester. While in vinylester dominant PVB, the influencing factor is spindle speed (44%).